(untitled) (Journal of the College of Basic Education, 2022)
Childhood is the first stage that a person goes through during his life, in which he is more susceptible to being affected by the factors surrounding him. The first five years of a child’s life are the period that leaves their mark on his personality and leaves an impact on him throughout his life. He joins kindergarten institutions that contribute to shaping and forming his personality. From all physical, kinetic, spiritual, mental and other aspects.